A PROSPECTIVE OBSERVATIONAL STUDY ON TOTAL KNEE REPLACEMENT OUTCOMES IN OSTEOARTHRITIC KNEES WITH VARUS DEFORMITY. - Dr. Ch Ramesh Babu; Dr. Banna Kiran Kumar; Dr. Kiran Kumar Joshi; Dr. Pradeep Kumar; Dr. Manoj Kumar (Student's Journal of Health Research Africa)
Background